Akses Puskesmas dan Kejadian Drop out Pasien Tuberkulosis Di Kabupaten Bantul Daerah Istimewa Yogyakarta - Ira Deseilla Pawa; Lutfan Lazuardi (Berita Kedokteran Masyarakat (BKM), 2020)
Background: In social perspective everyone have their rights to access health facilities (1) yet it still challenging due to geographical or non-geographical barriers. Inadequate access to health facilities has made the controlling of communicable disease not overly solved, including Tuberculosis. Indonesia have been put as country with the highest burden for TB, MDR TB and also TB/HIV in 2016-2020 (2). One of challenging that faced is the incidence of drug resistant TB due to TB treatment drop out. Bantul regency is the second highest TB cases finding rate after Sleman however, the cure rate below national standard during 2016-2018.Method: This study is observational descriptive research by using primary and secondary data, sample of this study consist of 27 community health centers and 60 auxiliary health centers. ArcGIS were used to analysis the spatial data.Results: The locations of community health centers in Bantul regency is near the collector road, the farthest distance to reach community health center in Bantul is 15 Km and the maximum travel time to community health is 60 minutes, geographical berries in Bantul regency are water body such as rivers and lakes. Human resource in 12 community health centers have been exceed the amount standards and 15 others have not been exceed the amount standards. Number of TB drop out was 22 cases, and Banguntapan village has highest amount of drop out TB cases.Conclusions: Community health distribution in Bantul regency is almost cover all the administrative area in Bantul regency. TB drop out cases is need serious intention to increase cure rate.Key words: Access, community health center, drop out tuberculosis, spatial pattern